The Imperial ambassador, the nuncio and the favourite: The Count of Pötting, Vitaliano Visconti Borromeo and Juan Everardo Nithard at the time of the Spanish crisis (1668–1669) (Theatrum historiae, 2019)
The essay aims at touching different aspects of Spanish policy during the regency of Mariana (1665–1675), the interest in the political and physical weakness of the heir to the throne Prince Charles and future King Charles II, the last Hapsburg on the Spanish monarchy. At that time, Madrid’s fate was mainly in the hands of three men: the Austrian Jesuit Nithard, the Count of Pötting, and the Apostolic nuncio, Vitaliano Visconti Borromeo.
Keywords: regency; Charles II; Spanish foreign policy; European diplomats